2000
DOI: 10.1016/s0005-2736(00)00251-0
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of lipid/DNA complexes during the freezing step of the lyophilization process: the particle isolation hypothesis

Abstract: The instability of nonviral vectors in aqueous suspensions has stimulated an interest in developing lyophilized formulations for use in gene therapy. Previous work has demonstrated a strong correlation between the maintenance of particle size and retention of transfection rates. Our earlier work has shown that aggregation of nonviral vectors typically occurs during the freezing step of the lyophilization process, and that high concentrations of sugars are capable of maintaining particle size. This study extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
147
3
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(168 citation statements)
references
References 30 publications
14
147
3
4
Order By: Relevance
“…Sugars isolate individual particles in unfrozen fraction and thereby prevent particle aggregation during freezing above Tg. Sugar vitrification is not required for this effect (54).…”
Section: Lyophilizationmentioning
confidence: 99%
“…Sugars isolate individual particles in unfrozen fraction and thereby prevent particle aggregation during freezing above Tg. Sugar vitrification is not required for this effect (54).…”
Section: Lyophilizationmentioning
confidence: 99%
“…Lyophilization is another method for addressing this problem and has been attested to be effective for long-term storage of nucleic acid formulations (7,13,14) and thus enables storage at room temperature. Besides cost reduction in transportation and storage, lyophilization is preferred over freezing due to better stability of biomolecules resulting from the removal of non freezable water associated with most biomolecules (15).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In the present study, we choose lyophilization for fabricating the miRNA reverse transfection formulations and demonstrated that this is able to load nucleic acid complexes onto a surface effectively and to make long-term storage of nucleic acid formulations possible. [23][24][25][26][27] Encouragingly, we found that the miRNA lipoplexes could be loaded onto the tissue culture plate surface evenly by lyophilization and that they could retain their intact structure. Lyoprotectants are generally used for lipoplex lyophilization, but it has been reported that ordinary lyoprotectants, such as glucose, can interfere with cell differentiation.…”
Section: Discussionmentioning
confidence: 83%
“…21,22 Lyophilization enabling long-term storage of nucleic acid formulations has recently been demonstrated to be able to load nucleic acid complexes onto surfaces. [23][24][25][26][27] Hence, reverse transfection formulations on a surface formed by lyophilization may provide an easy and efficient transfection approach for miRNA delivery. To our knowledge, although DNA and siRNAs have been plated on tissue culture plates for reverse transfection, there has been no such attempt using miRNAs.…”
Section: Introductionmentioning
confidence: 99%